Effect of hydrogen-rich water on periodontal disease, interleukin and blood glucose levels in diabetic - Albert Manggading HUTAPEA; Lina HADI (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Diabetes Mellitus (DM) is a metabolic disorder characterized by high blood glucose levelsassociated with periodontal disease and increased levels of inflammatory biomarkers such asinterleukin. Therapeutic effects of molecular hydrogen for a wide range of disease models and humandiseases have been investigated. This review aims to systematically analyze and review animal andhuman studies investigating the effect of HRW on periodontal tissues, interleukin, or blood glucoselevels. An electronic search was conducted via PubMed/Medline, Google Scholar, Wiley Online Library,LILACS, Science.gov, and Cochrane Central Register of Controlled Trials (CONTROL) using thekeywords "Hydrogen Water", "Diabetes Mellitus", "Interleukin" and "Periodontal disease" for studiespublished between January 2011 to May 2021. After the elimination of duplicate items, the primarysearch resulted in 101 articles. After excluding irrelevant articles based on abstract and title, full texts of45 articles were read to exclude additional unrelated studies. Eight studies were included in this reviewfor qualitative analysis. The results showed that Drinking HRW exerts certain antioxidants for oxidativegingival stress and anti-inflammatory effects by decreasing interleukin and decreasing blood glucoselevels for DM patients. KEYWORDS: HRW, DM, Periodontal disease, interleukin